Case Report: Benign Paroxysmal Positional Vertigo (BPPV) in Hypertension - Nastaghfiruka, Prita Aulia; Badriyah, Hanik; Handoko, Kun Avriady; Prajnaparamita, Irfani (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
A 58-year-old man who complained of dizziness spun around when the patient was in a sitting position, stood up and moved his head to look right and left that lasted for three days. To establish the diagnosis, we performed anamnesis with blood pressure results of 150/90mmHg, pulse 72x/ min, temperature 36.8 °C, breathing 22 x / minute. GCS 15 (E4 V5 M6). Physical examination of neurological otology yielded positive values on: Bidirectional nystagmus. The diagnoses we concluded were Benign Paroxysmal Positional Vertigo (BPPV) and Stage I JNC VII Hypertension, according to the results of the history and further examination that had been carried out. Further diagnosis and appeal, as well as treatment of both medical and non-medicated have been provided. The results of the analysis concluded that there is a close relationship between hypertension and BPPV.